Metabolomics reveals novel biomarkers of illegal 5-nitromimidazole treatment in pigs. Further evidence of drug toxicity uncovered. (15th May 2016) - Arias, M.; Chevallier, O.P.; Graham, S.F.; Gasull-Gimenez, A.; Fodey, T.; Cooper, K.M.; Crooks, S.R.H.; Danaher, M.; Elliott, C.T.
Highlights: Liver tissues of pigs, treated and non-treated with 5-nitroimidazole drugs, were biochemically profiled using LC–MS/MS detection. Multivariate statistical models positively differentiated controls from treated animals. Potential biomarkers, to identify the illegal use of 5-nitroimidazoles in pigs have been discovered. Abstract: The aim of the study was to investigate the potential of a metabolomics platform to distinguish between pigs treated with ronidazole, dimetridazole and metronidazole and non-medicated animals (controls), at two withdrawal periods (day 0 and 5). Livers from each animal were biochemically profiled using UHPLC–QTof-MS in ESI+ mode of acquisition. Several Orthogonal Partial Least Squares-Discriminant Analysis models were generated from the acquired mass spectrometry data. The models classified the two groups control and treated animals. A total of 42 ions of interest explained the variation in ESI+. It was possible to find the identity of 3 of the ions and to positively classify 4 of the ionic features, which can be used as potential biomarkers of illicit 5-nitroimidazole abuse. Further evidence of the toxic mechanisms of 5-nitroimidazole drugs has been revealed, which may be of substantial importance as metronidazole is widely used in human medicine.